Research on Optimizing Elevator Operation Management Strategy Based on Mathematical Model Algorithm - Zhu Rongzhen (SHS Web of Conferences)
This article aims to study the optimized configuration scheme of four elevators in a 33-story building, to achieve the optimization of waiting time and running time. By establishing mathematical models and utilizing computer simulation methods, analyze and optimize the operation strategy of elevators. This article will provide a detailed introduction to the design and implementation process of optimization algorithms, and verify their effectiveness and feasibility through specific examples.